Study on anisotropy in wire arc additively manufactured Inconel 625 multi-layered wall and its correlation with molten pool thermal history - Nagallapati, Vishwanath; Choudhary, Amit; Torris, Arun; Muvvala, Gopinath; Dadasaheb, Sagar Pawar; Gudur, Srinath Ellaswamy (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2022)
In the present study, the variation in molten pool thermal history with layer number during wire arc additive manufacturing of Inconel 625 wall was investigated. Further, its effect on the evolution of microstructure and anisotropy in mechanical and corrosion properties was reported. During the deposition process, the molten pool thermal history was monitored using a non-contact type IR pyrometer operating at 1.6 mu m wavelength. A total number of 40 layers were deposited, building a wall of 60 mm height. With an increase in layer number, the molten pool lifetime and cooling rate were found to increase and decrease, respectively, resulting in coarse grains and increased elemental segregation or Laves phase formation. To investigate its effect on mechanical properties, the samples were collected in a skewed fashion along the height with orientation in the deposition direction. The tensile specimens collected close to the substrate exhibited better strength and ductility, while the samples from the top location of the wall exhibited a relatively brittle mode of fracture, which was investigated by carrying out the fracture surface analysis using SEM. Corrosion test was also conducted along the height of the wall, wherein the samples close to substrate exhibited better corrosion resistance due to refined microstructure and low elemental segregations. Further, EDS, XRD analysis and hardness test were carried out to investigate the elemental composition, variation in phases and hardness with layer number, respectively.
Keywords: anisotropy; Layer number; mechanical properties; Molten pool thermal history; Wire arc additive manufacturing